Evidence for the interplanetary electric field effect on the OI 630.0 nm airglow over low latitude - Chakrabarty, D.; Sekar, R.; Narayanan, R.; Devasia, C.V.; Pathan, B.M. (My University, 2005)
[1] On a geomagnetically disturbed and non-spread F night (12 February 2004), the OI 630.0 nm airglow intensity variations recorded from Gadanki (13.5°N, 79.2°E, dip 12.5°) reveal quasi-periodic intensity fluctuations superimposed on the large-scale temporal variation during 1945–2315 Indian Standard Time (IST, IST = Universal Time (UT) + 5.5 hours). The residual airglow intensity fluctuations (after detrending the large-scale variation) with periodicities of ∼0.5 hours and ∼1.0 hours, respectively, are found to vary in accordance with the F layer height variations over the dip equator as well as with the Y-component of the interplanetary electric field (IEFy) variations calculated from the Advanced Composition Explorer (ACE) satellite data on 12 February 2004. Furthermore, these kind of periodic scale sizes in the residual airglow intensity fluctuations are not found on a geomagnetically quiet night (20 February 2004) and those intensity fluctuations do not show any correspondence with the F layer height variations over equator. Similar periodic components are also found in the temporal variations of instantaneous horizontal magnetic field (H) recorded at multiple stations over Indian subcontinent during the same interval on 12 February 2004. It is discussed that the currents responsible for the magnetic fluctuations are probably of magnetospheric origin. These observations using multiple techniques elicit the signature of the penetrating solar wind electric field in the nocturnal airglow intensity variations over low latitude during magnetically disturbed period.
Keywords: Interplanetary electric field; Advanced Composition Explorer (ACE); Magnetic field